Produtividade científica do Instituto Evandro Chagas contribuição para a saúde pública amazônica (2000-2020) - SILVA NETA, Clarice Pereira Barros da (Universidade Federal do Pará, 2024)
Instituto Evandro Chagas (IEC) located in the city of Belém in the state of Pará is an institution that develops research in the areas of Biological Sciences with a focusing on surveillance and public health in the Amazon. Facing the lack of studies shows the contribution of research to public health of the North region and Brazil, this research has the aim of analyze the scientific production of the Instituto Evandro Chagas, materialized in the scientific articles of the communities Arbovirology and Hemorrhagic Fever - Saarb, Parasitology - Sapar and Virology - Savir, from 2000 to 2020, available at Patuá Digital Repository. In order to reach its objective, this research used a descriptive and bibliographic approach of a quantitative and qualitative method and adopted as evaluation the metric studies on information under informetrics and data from the Notifiable Diseases Information System – SINAN. A total of 627 articles referring to Saarb, Sapar and Savir were collected in the Patuá Digital Repository and analyzed using production and collaboration indicators. Data showed that the academic profile is composed of 28,1 of researchers with degree in Biological Sciences and that 95.3% and 85.9% have master's and doctorate degrees. About interinstitutional collaboration, the sections maintain several national and international institutions connection that develop research on the themes identified in the surveys, which are connected with the epidemiological surveillance actions of SUS, referring to the notification of diseases and public health problems. The study demonstrated the importance of the research conducted for public health and highlighted the importance of Instituto Evandro Chagas as a relevant research center for the northern region and for Brazil which has contributed to Amazonian public health by allowing knowledge of the nosology of diseases and improvement in health surveillance actions for the population of the Amazon region and Brazil.